EFFECTS OF ASCORBIC ACID ON MEMBRANE STABILITY AND YIELD OF HEAT-STRESSED BT COTTON - M. A. Kamal; M. F. Saleem1; M. A. Wahid; A. Shakeel (Journal of Animal and Plant Sciences, 2017)
Among all the environmental factors heat stress has a key role in growth and yield reduction of cotton crop (Gossypium hirsutum L.). The present study was carried out to look into the effects of foliar applied ascorbic acid on cotton crop grown under heat stress condition. Experiment was planted during 2013 and repeated during 2014 at the Agronomic Research Area, University of Agricultural Faisalabad, Pakistan. Experimental material was comprised of heat stress imposition (H0= No heat imposition, H1= Heat imposition at square initiation, H2= Heat imposition at flower initiation) and levels of foliar applied ascorbic acid (A0= control/water spray, A1= 20 mg L-1, A2= 40 mg L-1 and A3= 60 mg L-1). Heat was imposed to cotton crop by covering the plots with polythene sheet at reproductive stages for 5 days. Results showed that heat stress badly affected the yield and related components of cotton crop. Cell membrane thermostability (CMT) was also reduced under high temperature stress. Foliar application of ascorbic acid at 40 mg L-1 reduced the cell injury and improved yield and related components under all heat treatments.
Keywords: Gossypium hirsutum; heat tolerance; sympodial branches; boll weight; boll number